Development of Student Worksheets Based on Socio-Scientific Issues (SSI) on Climate Change Materials for Junior High School Students - Meli Ameliawati; Ading Permadi; Meti Maspupah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
This research is motivated by the lack of development of Socio-Scientific Issues-based worksheets, especially on materials related to social and environmental issues, so the purpose of this study is to analyze student responses to the development of Socio-Scientific Issues-based worksheets on climate change materials. The research method used is Research and Development (R&D) research with a 4-D development model modified to 3-D. The implementation only reaches the product development stage due to time constraints and the Covid-19 pandemic. Research data analysis is generally obtained from literature studies and field studies. Field studies were obtained from research conducted on 30 class VII students of SMP Negeri 1 Cisalak in the even semester of the 2020/2021 academic year using an initial needs analysis questionnaire and a student readability response questionnaire the worksheet that had been made. After the revision and evaluation of the draft results, the worksheet SSI is ready to be used for research. From the results of the student readability questionnaire on the SSI worksheet, the average result of the readability assessment was 90%. The results obtained that the SSI worksheet developed in the very valid category and suitable for science learning class VII, especially on climate change material. Researchers recommend that Socio-Scientific Issues (SSI)-based worksheets can be an alternative learning, especially on science and environmental problems materials.